Facing dengue fever – our first experience - Cvjetković, Dejan Miroslav; Stefan Mikić, Sandra; Hrnjaković Cvjetković, Ivana B. (Vojnosanitetski pregled, 2017)
Introduction. Dengue fever is a mosquito-borne disease caused by dengue virus, endemic in tropical and subtropical regions, where it is mostly imported from. The most common clinical form is classic dengue fever. We presented the first dengue case microbiologically confirmed in Serbia. Case report. A 34-year-old male got classic dengue fever after arrival from Cuba. The disease occurred suddenly with fever, myalgias, skin rash, hepatosplenomegaly, cytopenia, abnormal aminotransferase and creatine kinase levels. The diagnosis was confirmed with virological diagnostic methods. Significant leukopenia and thrombocytopenia as well as elevation of serum creatine kinase activity were recorded from the very beginning of hospitalization, but were gradually normalized. The whole duration of hospitalization was accompanied by laboratory signs of liver lesion. The disease had favourable outcome. At hospital discharge, the patient was afebrile, asymptomatic, with discrete erythematous rash on torso and arms, normal hemathological values and creatine kinase level and moderately elevated alanine-aminotransferase level. Conclusion. Considering global climate changes and growing international traffic, our health care service needs to be ready for possible massive outbreaks of dengue and other tropical infectious diseases in forthcoming years.